Implementasi Manajemen Strategis dalam Meningkatkan Peran Serta Masyarakat di SMK Darur Roja Cinere Depok - Ukat Suhaedi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to analyze the implementation of strategic management in enhancing community participation at SMK Darur Roja Cinere Depok. The research was motivated by the low level of active community involvement in educational activities, particularly in faith-based vocational schools. Using a qualitative approach and case study method, data were collected through in-depth interviews, participatory observations, and documentation. The findings indicate that strategy formulation was conducted participatively, involving the principal, teachers, the school committee, and the surrounding community. The strategic implementation included various collaborative programs such as